1983
DOI: 10.1111/j.1365-2265.1983.tb02878.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Plasma Exchange for Graves' Ophthalmopathy

Abstract: Eighteen patients with ocular manifestations of Graves' disease were treated by plasma exchange. Detailed clinical, ophthalmological and orthoptic assessments were made including computerized axial tomography and A + B scan ultrasound of the orbits. Seventeen different ocular parameters were separately rated for each patient. The changes recorded were small, statistically insignificant, and no patient was cured of ocular disease. There were no significant correlations between the ocular changes recorded and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Favorable results were also reported by Berlin et al (154), who observed a reduction of the OI in 9 (69%) and of subjective symptoms in 10 (77%) of 13 patients; azathioprine was concomitantly administered to 8 patients, and 2 patients needed further sessions of plasmapheresis. In contrast, unfavorable effects of plasmapheresis were reported in other series (155,156). In summary, plasmapheresis provided conflicting results, since both favorable effects and treatment failures were reported.…”
Section: Plasmapheresismentioning
confidence: 41%
“…Favorable results were also reported by Berlin et al (154), who observed a reduction of the OI in 9 (69%) and of subjective symptoms in 10 (77%) of 13 patients; azathioprine was concomitantly administered to 8 patients, and 2 patients needed further sessions of plasmapheresis. In contrast, unfavorable effects of plasmapheresis were reported in other series (155,156). In summary, plasmapheresis provided conflicting results, since both favorable effects and treatment failures were reported.…”
Section: Plasmapheresismentioning
confidence: 41%
“…The most significant effects were on soft tissue involvement, proptosis, intraocular pressure, and visual acuity [228]. In contrast to these, unfavorable effects of plasmapheresis have been reported [229,230]. Trials involving plasmapheresis provided conflicting results.…”
Section: Plasmapheresismentioning
confidence: 99%
“…Cyclophosphamide has proved beneficial in patients with optic neuropathy, diplopia and chemosis (Bigos et al 1979, Wall et al 1979, and this agent would seem worthy of further investigation. Plasma exchange was recently evaluated in 18 patients and found to be of no benefit (Kelly et al 1983). This is an important finding in terms of the aetiology, since it provides indirect evidence that serum autoantibodies are unlikely to be involved in the production of the eye disease.…”
Section: Treatmentmentioning
confidence: 99%